IKAL’S STRUGGLE OF LIFE IN ANDREA HIRATA’S RAINBOW TROOPS: Struggle of Life - Leliana Lestari Sain; Risma Kartika Dewi (Fakultas Sastra Universitas Gresik, 2022)
Struggle is one of the keys to success in life. If there is a struggle there must be success because success requires struggle or effort in life. In this research, the researcher analysis the Ikal’s struggle of life to become a successful person and factors influence Ikal to become a successful person. Objective of this study are to describe the Ikal’s truggle of life to become a successful person and to describe the factor influence Ikal to become a successful person. The purpose of this research is to illustrative evidence of life struggle in Ikal’s life. The method used in this research is descriptive qualitative. Data source used in the research is from conversations and paragraphs in the novel. Data collection procedures in the research are reading and understanding novel, categorizing and classifying the data and organizing the data. The result of the research indicated that Ikal’s struggle to get a master’s degree from European Union as has brought him to be a successful person are that Ikal always studied, read as many books whenever and wherever, he spends his time only studied to pass the scholarship. The factors do influence Ikal to become a successful person are competitive personality (Ikal having a very competitive spirit/ personality), working harder than most people and fate.